BRCAness and prostate cancer: diagnostic and therapeutic considerations. Issue 4 (November 2018) - Dhawan, Mallika; Ryan, Charles
Abstract Background: Recent advances in genetic sequencing and recent studies focusing on the broader use of Poly ADP Ribose polymerase (PARP) inhibitors have led to an upsurge of interest in DNA repair mutations as they relate to prostate cancer. Methods: This review outlines ongoing studies and recent publications as they relate to the prevalence and detection of DNA repair mutations in metastatic prostate cancer. The detection of these mutations through multiple diagnostic approaches is discussed, including germline sequencing, somatic sequencing, cell-free DNA assays, and circulating tumor cell assays. The clinical course of patients with prostate cancer and DNA repair gene mutations is explored in addition to therapeutic strategies for this population. Conclusions: In men with metastatic prostate cancer, it is reasonable to obtain germline genetic sequencing as well as somatic tumor genomic sequencing to help guide further treatment decisions that may include PARP inhibitors or carboplatin in the future. In the future, in men with metastatic castrate resistant prostate cancer with progression on PARP inhibitors, cell-free DNA sequencing may help elucidate mechanisms of resistance, which include reversion mutations.